Economic and Environmental Comparison of the Monosodium Glutamate (MSG) Production Processes from A-Molasses in an Integrated Sugarcane Biorefinery - Abdul M. Petersen; Jeanne Louw; Johann F. Görgens (International Journal of Chemical Engineering)
Due to unfavourable market conditions, the sugar industry is looking to diversify its product portfolio by producing economically feasible and environmentally sustainable products in addition to crystalline sugar. The production of monosodium glutamate (MSG) from sugar is a well-established commercial process, and a new local production facility could be a potential low-risk diversification option for the South African sugar industry. While the consumption of MSG has been a controversial topic due to possible negative health effects, the global market, especially in developing and sugar-producing countries such as China, Indonesia, and Vietnam is growing at a cumulative annual growth rate (CAGR) of 6.2%. In this study, the economic feasibility and environmental sustainability performance of the production of monosodium glutamate (MSG) from A-molasses in a biorefinery annexed to a typical sugar mill are assessed. Five different process scenarios were investigated, including three indirect (two-pot) processing routes through glutamic acid fermentation and two one-pot conversion scenarios. The indirect scenarios include the conventional route with fertiliser as a byproduct; second, the conventional route with fertiliser and animal feed as byproducts; and third, a state-of-the-art membrane-assisted nanofiltration method with animal feed and fertiliser as byproducts. The one-pot scenarios include syrup being sold as a byproduct or syrup being recycled back to the fermenter. The three indirect process scenarios resulted in the highest minimum selling price (MSP) of approximately 1.8 US$/kg and the highest greenhouse gas (GHG) emission potential of around 0.64 kgCO2/kgMSG. Development of a more direct (one-pot) conversion process can reduce the MSP to 1.6 US$/kg, which is close to the current market price and reduce the GHG emissions to 0.55 kgCO2/kgMSG, if the fermentation microbe can convert sugars to glutamate efficiently in the presence of high sodium ion concentrations.